ANALISIS KONSUMSI RUMAH TANGGA NELAYAN DI KELURAHAN BONEOGE KECAMATAN BANAWA KABUPATEN DONGGALA - Zulkifli Zulkifli (Katalogis, 2016)
This study aims to: (1) Determine the influence of income on household consumption fishing in the Village Boneoge Banwa District of Donggala; (2) Determine the amount of household consumption expediture village fisherman Boneoge Banawa District of Donggala; and (3) to analyze the proportion of consumption expeditures of the proportion of household income fisherman Village Boneoge Banawa District of Donggala. This research is a descriptive study with a sample ot the study were 42 people chosen by purposive sampling. Data were analyzed using simple linear regression analysis and analysis of consumption. Result of the study concludes that: (1) income affect household consumption fishing in the Village Boneoge Banawa District of Donggala; (2) The amount of consumption of the majority of households in the village fisherman Boneoge Banawa District of Donggala equal to the amount of its income in each month; and (3) proportion of consumption expediture on household income fisherman in the Village Banawa District of Donggala largely allocated to meet the needs of food family.